Pengaruh Kinerja dan Profesionalisme Kerja Pegawai terhadap Kualitas Pelayanan Publik pada Badan Kesatuan Bangsa dan Politik Kota Banjarmasin - Raisa Nurrahima Pratiwi; Purboyo Purboyo; Teguh Wicaksono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine and analyze: (1) Performance affects the quality of public services at the National and Political Unity Agency of Banjarmasin City, (2) Employee Work Professionalism affects the Quality of Public Services at the National and Political Unity Agency of Banjarmasin City, (3) Performance and Professionalism of Employee Work affects the Quality of Public Services Badan Kesatuan Bangsa dan Politik in Banjarmasin. The approach used in this study is using a quantitative approach. The population in this study amounted to 30 people who were sampled in this study using saturated sampling techniques. Data were collected using questionnaires measured using Likert scales. Data processing using the SPSS computer program version 26.0. The results of the study proved that partially (1) performance did not have a positive and significant influence on the quality of public services, (2) work professionalism had a positive and significant influence on the quality of public services and (3) work performance and professionalism had a positive and significant influence on the quality of public services.